18F-FDG PET-CT incidental lung findings in asymptomatic COVID-19 patients: evidences from the Italian core of the first pandemic peak - Alice Bonanomi; Pietro Andrea Bonaffini; Marianna Spallino; Ludovico Dulcetta; Paolo Niccolò Franco; Clarissa Valle; Paolo Marra; Andrea Bruno; Sandro Sironi (Asia Oceania Journal of Nuclear Medicine and Biology, 2022)
Objective(s): To illustrate incidental 18F-FDG PET-CT findings and related CT alterations of suspicious pulmonary interstitial involvement in asymptomatic oncologic patients during the first COVID-19 outbreak in the core of Italian peak. Methods: We retrospectively evaluated the 18F-FDG PET-CT follow-up examinations performed during the first Italian COVID-19 outbreak (March 3rd-April 15th, 2020) in 10 asymptomatic oncologic patients with a highly suspicious interstitial pulmonary involvement on CT. Six cases were confirmed SARS-CoV-2 by molecular tests. The following parameters were assessed: 1) lung involvement on co-registration CT as extension (laterality, number of lobes), pattern (ground-glass opacities/GGO, consolidations, mixed) and stage (early, progressive, peak, and absorption); 2) the maximum standardized uptake value (SUVmax) of lung lesions on 18F-FDG PET. Results: The involved lobes were 5 in 5 cases (3 confirmed SARS-CoV-2), 2-4 in 4 cases and 1 in 1 case. GGO were found in all patients; 3 cases also showed a combination of GGO and peripheral consolidations (mixed). Five cases were suggestive for an early stage of interstitial pneumonia, 4 for progressive and 1 for peak. All the lung lesions showed increased FDG uptake. In early stages SUVmax ranged from 1.5 to 11, in progressive from 3.3 to 6.8, in peak from 2.4 to 7.7. SUVmax ranged 1.5-11 in patients with only GGO and 2.8-7.7 in those with mixed pattern. Conclusions: 18F-FDG PET-CT findings in suspected COVID-19 pulmonary involvement of asymptomatic oncologic patients showed an increase in FDG uptake of GGO and consolidations, but with a wide and apparently nonspecific range of SUVmax values.